Uji Aktivitas Antibakteri Ekstrak Jahe (Zingiber officinale) terhadap Mikroorganisme pada Tape Ketan Putih - Shafitri Shafitri; Ardi Mustakim (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
White glutinous rice fermentation (tape ketan putih) is a traditional food product containing various microorganisms, including Gram-positive bacteria that may act as contaminants and reduce product quality. Ginger (Zingiber officinale) contains active compounds such as gingerol and shogaol, known for their antibacterial properties. This study aimed to evaluate the antibacterial activity of ginger extract against microorganisms isolated from white fermented glutinous rice. Methods: Ginger extract was obtained by maceration using ethanol as a solvent and tested by disk diffusion method on Nutrient Agar against isolated microorganisms. Results: An inhibition zone was observed around the ginger extract disk, indicating moderate antibacterial activity against Gram-positive bacteria. Conclusion: Ginger (Zingiber officinale) extract shows potential as a natural antibacterial agent against Gram-positive bacteria in tape ketan putih and may be developed as a natural preservative for fermented products.